Potential for an aquaculture industry in Trinidad and Tobago (Institute of Marine Affairs St. JamesTT, 1981)
Looks at the environmental and economic potential which exists for an aquaculture indutry in Trinidad and Tobago. Examines suitable species with potential for culture locally.
DC